Analysis of the Influence of Digital Marketing and Customer Relationship Management on Sales Levels of MSME Products in Dompu Regency - Nurlaila, Nurlaila; Mansyuri, M. Ikhwan; Rubiyanti, Desi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aims to determine and analyze the influence of digital marketing and Customer Relationship Management on the level of sales of UMKM products in Dompu Regency. The research method used in this research is quantitative research, with a descriptive approach. The quantitative data collection technique in the research used a questionnaire with a saturated sample of UMKM registered on the website of the Dompu Regency Cooperatives and UKM Service. And analyze the data using SPSS tools. The results of this study indicate that both digital marketing and customer relationship management have a positive and significant effect on the increase in UMKM product sales, both partially and simultaneously. The t-test shows that digital marketing has a significance value of 0.004 and CRM has a significance value of 0.000, both of which are significant at the 95% confidence level. The F-test shows a significance value of 0.000, indicating that both variables jointly have a significant effect on sales. The coefficient of determination (R²) is 0.628, indicating that 62.8% of the variation in UMKM sales can be explained by the combination of digital marketing and CRM.